Reward Network Modulation as a Mechanism of Change in Behavioral Activation. Issue 2 (March 2020) - Nagy, Gabriela A.; Cernasov, Paul; Pisoni, Angela; Walsh, Erin; Dichter, Gabriel S.; Smoski, Moria J.
Behavioral Activation (BA) is a contemporary third-wave psychosocial treatment approach that emphasizes helping individuals become more active in ways that are meaningful to them as a means of improving mood and quality of life. BA has been designated as a well-established, validated treatment for depression by the American Psychological Association following several decades of accumulated empirical support demonstrating that BA techniques successfully reduce depression symptoms and produce other desirable outcomes across a variety of populations and contexts. The purported mechanism of change underlying BA treatment lies in increasing activation, which in turn increases contact with positive reinforcement thereby reversing the cycle of depression. Current studies are further investigating how increasing activation and subsequent contact with mood reinforcers can influence mood and behavior. Specifically, there is growing evidence that BA modifies function of reward-related networks in the brain, and that these changes are associated with clinical improvement. Herein, we provide a brief history of BA, describe the primary components of BA treatment, and describe BA's purported mechanisms of change at behavioral, neural, and subjective activation levels. We present limitations as well as gaps in the current state of knowledge regarding mechanisms of action of BA.